Hyperspectral downward sky leaving radiance observed at 45° zenith angle during cruise M148/2 aboard RV METEOR - Shungudzemwoyo Pascal Garaba; Claudia Thölen; Timothy G Ferdelman; Oliver Zielinski (PANGAEA, 2020)
Automated continuous above-water hyperspectral calibrated radiometric quantities were observed in the international waters of the Atlantic Ocean during the scientific field campaign M148/2 aboard RV METEOR. The cruise began on 02 July 2018 from Walvis Bay, Namibia and was completed on 20 July 2018 in Las Palmas de Gran Canaria, Spain. A radiometer setup, with two TriOS RAMSES-ACC hyperspectral cosine irradiance meters to measure incoming solar irradiance, four TriOS RAMSES-ARC hyperspectral radiance meters to measure total upward sea surface leaving radiance Lsfc at 45° nadir and sky-leaving radiance Lsky at 45° zenith angle, was installed using a custom-made frame at the bow of RV METEOR. The frame was attached to the bow of the ship with the radiance meters having a 90° azimuthal angle separating them. Quality control involved retaining the Lsfc observations with lowest values (Garaba et al., 2012; Garaba et al., 2015). Data logging was automated using TriOS MSDA XE version 8.9.2 software and further processing was done using Mathworks Matlab 2016a and R software. Processed data was interpolated to 1 nm spectral resolution using PCHIP function in Matlab between 320 and 950 nm. Raw data is available on request.